Nitric Oxide-Releasing Dendrimers as Antibacterial Agents - Sun, Bin (2012)
The antibacterial activity of a series of nitric oxide (NO)-releasing poly(propylene imine) (PPI) dendrimers was evaluated against both Gram-positive and Gram-negative pathogenic bacteria, including methicillin-resistant Staphylococcus aureus. A direct comparison of the bactericidal efficacy between NO-releasing and control PPI dendrimers (i.e., non-NO-releasing) revealed both enhanced biocidal action of NO-releasing dendrimers and reduced toxicity against mammalian fibroblast cells. Antibacterial activity for the NO donor-functionalized PPI dendrimers was shown to be a function of both dendrimer size (molecular weight) and exterior functionality. In addition to minimal toxicity against fibroblasts, NO-releasing PPI dendrimers modified with styrene oxide exhibited the greatest biocidal activity (≥9.999% killing) against all bacterial strains tested. The N-diazeniumdiolate NO donor-functionalized PPI dendrimers presented in this study hold promise as effective NO-based therapeutics for combating bacterial infections.